RUANG BANACH PADA RUANG BARISAN l1, lp DAN l - Alwi, Wahidah (Fakultas Sains dan Teknologi UIN ALauddin, 2014)
The main object of the vectors are the vectors can be added together and generate a vector, and produces a number is multiplied by another vector. Any set of objects with properties like this are called